Penerapan Model Reward And Punishment Berbantuan Media Pahuanca Untuk Meningkatan Hasil Belajar Peserta Didik - Annisya' Qona'ah; Wawan Shokib Rondli; Lintang Kironoratri (PGSD Universitas Muria Kudus, 2023)
The purpose of this study was to improve the learning outcomes of third grade students at SD 2 Getas Pejaten through the application of the reward and punishment model assisted by Pahuanca media.This research uses a type of classroom action research that will be carried out at SD 2 Getas Pejaten. The subjects of this study were class III students with a total of 19 students. This classroom action research was conducted in 2 cycles and each cycle consisted of 2 meetings with the stages of planning, implementing, observing and reflecting. This data collection technique uses test techniques and non-test techniques. The instrument used is a test instrument in the form of evaluation questions, while the non-test instrument is in the form of student activity observation sheets. Data analysis of this research was obtained using quantitative and qualitative techniques.The results of this study indicate that there is an increase in student learning outcomes with the application of the reward and punishment model assisted by the Pahuanca media. The evaluation results on students' PPKn content obtained a class average of 83.68 with a completeness percentage of 89.47%. Whereas in Indonesian content, the class average was 82.63 with a percentage of students' completeness of 94.74%. The application of the reward and punishment model with the help of Pahuanca media can improve student learning outcomes in the sub-theme of climate change for class III SD 2 Getas Pejaten.